Sedimentology of the Basal Section of the Montezuma Formation (Plio-Pleistocene), Cóbano, Puntarenas, Costa Rica - Obando-Acuña, Luis G. (2026)
The lithofacies of coastal cliffs are documented in the Catarata (C) section of the Quebrada El Chorro, the Punta Quizales (Q) section, and the Acantilado (A) section in the Cóbano area of the Nicoya Peninsula, Costa Rica. The surveyed sections are stratigraphically correlated with the basal facies of the Montezuma Formation from the Middle Pliocene to the Early Pleistocene. Sedimentologically, these facies are characterized by strong lithological variability, both vertically and laterally, ranging from shallow marine to transitional coastal sediments, including fine to coarse sandstones and conglomerates. The facies association is related to environments such as river mouths in intertidal coastal plains, beaches, and fan deltas. At least two stages of marine transgressions were defined. A third stage is not well defined in the studied sedimentological sections and could not be characterized. The present-day coastal cliffs show evidence of significant regional tectonic uplift, and consequently, a marked relative fall in sea level and erosive retreat caused by wave action.